Christian Identification and Self-Reported Depression: Evidence from China - Hu, Anning (Journal for the scientific study of religion, 2017)
The nexus between religion and mental health in the East has been understudied, where the coexistence of multiple religions calls for scholarly attention to religious identification. This article investigates the impact on self-reported depression of an individual's identification with Christianity in a non-Judeo-Christian and religion-regulating social setting. Taking advantage of the Chinese General Social Survey 2010, our empirical analyses suggest that people who explicitly identify with Christianity report a significantly higher level of depression compared with both religious nones and self-claimed Buddhists. In contrast, there is no significant difference in self-reported depression between religious nones and self-identified Buddhists. This study supplements current literature on the connection between religious affiliation and mental health with a particular interest in East Asia, suggesting that the consequence on mental health of religious identification is contingent on a religion's social status, and a religion's marginal position may turn religious identification into a detrimental psychological burden.